2003
DOI: 10.1196/annals.1299.143
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Apoptosis in Human Pancreatic Cancer Cells by Docosahexaenoic Acid

Abstract: Polyunsaturated fatty acids have been indicated to induce anti-proliferative and/or apoptotic effects in various tumor cells. We showed that, at a 200- micro M concentration, both alpha-linoleic (18:2 n-6; LA) or docosahexaenoic (22:6 n-3; DHA) acid inhibited cell growth, while only DHA induced apoptosis in the human Paca-44 pancreatic cancer cell line. Investigating the mechanism underlying DHA-induced apoptosis, we showed that DHA induced a rapid and dramatic (>60%) intracellular depletion of reduced glutath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 14 publications
0
18
0
Order By: Relevance
“…Both ROS and RNS induce DNA damage and DNA strand breaks. Merendino et al [35] showed that DHA induced oxidative stress by depleting intracellular glutathione (GSH) in Paca-44 pancreatic cancer cells. They suggested that GSH depletion occurred via active GSH extrusion in cancer cells, since the inhibition of GSH efflux by treatment with the specific inhibitors of carrier-mediated GSH extrusion, cystathionine or methionine, completely reversed the apoptosis.…”
Section: Dha Induces Oxidative Stress and Oxidative Dna Damage To mentioning
confidence: 99%
“…Both ROS and RNS induce DNA damage and DNA strand breaks. Merendino et al [35] showed that DHA induced oxidative stress by depleting intracellular glutathione (GSH) in Paca-44 pancreatic cancer cells. They suggested that GSH depletion occurred via active GSH extrusion in cancer cells, since the inhibition of GSH efflux by treatment with the specific inhibitors of carrier-mediated GSH extrusion, cystathionine or methionine, completely reversed the apoptosis.…”
Section: Dha Induces Oxidative Stress and Oxidative Dna Damage To mentioning
confidence: 99%
“…However, even though limited in number, the available studies strongly suggest the efficacy of these nutraceutical compounds against the growth of several other cancer cells, including those of pancreatic [116,117], lung [32], prostatic [118][119][120], hepatic [63,121,122] and nervous [123] origin.…”
Section: Cancer Cells Of Other Originmentioning
confidence: 99%
“…These names reflect the type of cell from 260 which the cancer developed [49]. pancreatic cancer and assuming a causality between dietary con-289 tent of n-6 PUFAs and carcinogenesis [55,56]. Thus an increased 290 incidence of pancreatic cancer and liver metastasis was achieved 291 by a dietary modification [55].…”
Section: Introductionmentioning
confidence: 98%
“…pancreatic cancer and assuming a causality between dietary con-289 tent of n-6 PUFAs and carcinogenesis [55,56]. Thus an increased 290 incidence of pancreatic cancer and liver metastasis was achieved 291 by a dietary modification [55]. While CLA is regarded as an essen- Liver cancer or hepatic cancer is a cancer that originates in the 329 liver [54].…”
Section: Introductionmentioning
confidence: 99%